Impact of Classroom-Based Fluency Instruction on Grade One Students in an Urban Elementary School - Timothy V. Rasinski; Randy Yates; Kelly Foerg; Kelly Greene; David Paige; Chase Young; William Rupley (Education Sciences, 2020)
The present exploratory study examined the effect of the implementation of a reading fluency instruction protocol on the reading performance of early first grade students in an urban school. Previous research has tended to examine the effects of fluency instruction after students have achieved some degree of competency in word recognition, usually toward the end of first grade and beyond. The fluency instruction provided in this study included repeated and assisted reading and was delivered daily over a ten-week period in the first semester of the school year by classroom teachers. The reading performance of students in the fluency instruction group (n = 51) was compared with a comparable group of first grade students (n = 27) who did not receive the fluency instruction, though the total number of minutes devoted to daily reading instruction and home reading was equal between groups. Descriptive analyses of pre- and post-testing data suggest that the first grade students receiving the fluency instruction made substantive, but not statistically significant, gains in reading achievement over the comparison group of students not receiving fluency instruction. The results suggest that dedicated and systematic fluency instruction may be appropriate for students before high levels of word decoding are achieved and that fluency instruction may be an effective instructional protocol as early as the beginning of first grade. Given the acknowledged limitations, including small sample size, further research into fluency instruction in early first grade is recommended.